4CPS-091 Variation of the hiv-naÏve patient profile and initial art recommended regimens after implementation of the universal treatment recommendations in a university hospital. (2nd March 2018) - Monge, I; Luque, S; Gonzalez, E; Ferrandez, O; Barcelo, J; Fernandez, X; Antonio, M de; Carballo, N; Knobel, H; Grau, S
Abstract : Background: According to current guidelines, antiretroviral therapy (ART) is recommended for all HIV-infected individuals, regardless of the symptomatology and the CD4 T lymphocyte cell count. In addition, initial combination regimens have been updated in the past years considering the combination of two NRTIs with an INSTI the preferred therapy. These updates may have led to a change in the naïve-patient profile and the selection of initial ART regimens. Purpose: The aim of the study is to compare the naïve-patient profile and the prescribed initial ART regimens before and after the implementation of the universal treatment recommendations in our hospital. Material and methods: Retrospective study performed in a third-level university hospital with a cohort of approximately 1, 800 HIV-infected patients on ART. We included HIV-naïve patients who bergan ART from January 2014 to August 2017. Collected data: demographics, hepatitis C virus (HCV) and hepatitis B virus (HBV) coinfection, HIV-RNA (viral load) and CD4 cell count at the start of the ART, and initial ART regimen. Data were compared by classifying the patients into two groups: those who started ART before July 2015 (pre-recommendation) and subsequently (post-recommendation). Statistics: categorical variables, n (%), quantitative variables and mean ±SD. Comparison of variables: t-student test, χ² test. Results: Patients who started ART: 273 (129 pre-recommendation and 144 post-recommendation). Pre-recommendation/post-recommendation. Male, n (%): 115 (89.1)/128 (88.9), P-value>0.999. Age, mean ±SD: 38.3±9.9/37.3±9.6, P-value=0.415. HBV, n (%): 17 (13.2)/21 (14.6), P-value=0.861. HCV, n (%): 31 (24.0)/19 (13.2), P-value=0.028. CD4 (cells/ml), mean ±SD: 350.5±239.90/420. 2±314.4, P-value=0.042. Viral load (copies/ml), mean ±SD: 209, 407.1±901, 5690.6/383, 251. 3±1, 505, 390, 8, P-value=0.243. Type of ART, n (%), P-value<0.001. 2 NRTIs+NNRTI: 42 (32.8)/3 (2.1). 2 NRTIs+PI: 39 (30.5)/21 (14.6). 2 NRTIs+INSTI: 47 (36.7)/120 (83.3). *One patient began NNRTI+PI (excluded from the analysis). Conclusion: Naïve patients who have began ART in the past 2 years have a higher CD4 cell count, which is in line with new guidelines for treatment initiation regardless of their immunological status. A lower percentage of HCV coinfection was observed among HIV–naïve patients in the post–recommendation period. The initial ART regimen has varied considerably and nowadays the combination of two NRTIs plus an INSTI is the selected therapy in more than 80% of naïve patients. These results show a high adherence to the current guidelines in our centre. No conflict of interest